ASPEK BIOKULTURAL SISA RANGKA MANUSIA DARI SITUS LIANGAN, TEMANGGUNG, JAWA TENGAH - Sofwan Noerwidi (Berkala Arkeologi, 2016)
In 2013, Center for Archaeological Research of Yogyakarta has found a human remain in Cluster F, Liangan site, Temanggung, which named as individual of Liangan F1. This study tries to reveals biological and cultural aspects which recorded on this remain by bioarchaeological approach. Biological aspects are including; age estimation, sex determination, population affinity, and pathology or health condition. Meanwhile, cultural aspects are including antemortem cultural practice which associated to dental modification, and perimortem taphonomy as evidence of funeral practices or burial procedures. Study on human remains from Liangan settlement site of Ancient Mataram Kingdom has opened our knowledge to understanding culture and human behavior which develop during the historical period of 9th-10th century AD in Java.